Stabilization of Zn Metal Anode through Surface Reconstruction of a Cerium‐Based Conversion Film. (17th September 2021) - Deng, Canbin; Xie, Xuesong; Han, Junwei; Lu, Bingan; Liang, Shuquan; Zhou, Jiang
Abstract: Corrosion and dendritic deposition have been the long‐standing interfacial challenges of Zn anode, resulting in the deterioration of the aqueous zinc‐based batteries. Herein, the surface of Zn metal anode is pioneeringly reconstructed by a cerium‐based conversion film (Zn@CCF) through a chemical conversion method. Faster growth of the film in the vicinity of zinc grain boundaries significantly prevents the substrate from genetic micro‐corrosion that leads to catastrophic damage. The affinity of the film toward zinc facilitates a low nucleation barrier and smooth zinc deposition. Consequently, Zn@CCF enables long‐term lifespan (1200 h) with low polarization (≈ 60 mV) at 4.4 mA cm −2, which also maintains good capacity retention and excellent cycling stability of Zn@CCF/MnO2 full cells. This facile and effective approach helps suppress Zn dendrite formation and brings forward the significance of surface reconstruction of the Zn metal anode for corrosion inhibition, which can be potentially applied to other metal anodes in aqueous energy storage systems. Abstract : A uniform and compact cerium‐based conversion film is constructed on Zn metal anode through a facile chemical conversion method, which can effectively prevent Zn metal from severe corrosion and dendritic Zn deposition. Higher specific capacity and better cycling stability can be achieved for symmetrical cells and full cells with this kind of Zn metal anode.